Low-RCS and beam-steerable dipole array using absorptive frequency-selective reflection structures - Huang, Hao (2021)
This communication presents an approach to design a beam-steerable dipole array with low radar cross section (RCS). A 2-D periodical array of dipole antennas is colocated with absorptive frequency-selective reflection (AFSR) structures to effectively reduce the out-of-band RCS and maintain high gain at the in-band frequencies. The AFSR structures consist of 3-D bandstop frequency-selective structure (FSS) and pyramidal-shaped absorbers to provide a reflection band for the dipole array with enhanced front-to-back ratio. Compared with the reference array, the radiation performance of the proposed array is maintained with an aperture efficiency of 70% and a measured peak gain of 21.5 dBi. The beam-steering angle is up to ±45°. Meanwhile, more than 10 dB two-sided out-of-band RCS reduction is achieved with a bandwidth of 96.5% and 30% for copolarization and 142% for cross polarization, and the in-band RCS is unchanged.